Reducing the environmental footprint of livestock production - Frija, Aymen; Notenbaert, An Maria Omer; Yigezu, Yigezu Atnafe; Alary, Veronique; Mannai, Amai (International Livestock Research Institute, 2024)
Livestock production takes up approximately 77% of the world’s agricultural land, or about 3.4 billion hectares, primarily for feed production. This extensive land use represents a significant opportunity cost, as it could otherwise be used to conserve biodiversity, such as wetlands and forests, produce cash and food crops or sequester carbon. Current use limits the potential for preserving different biomes and enhancing biodiversity, leading to land degradation due to overgrazing and poor nutrient or fertilizer management. Additionally, livestock production is water-intensive and a major source of water pollution caused by run-off from fertilizers, pesticides and animal waste. As a result, livestock is considered a significant contributor to global environmental degradation, impacting climate change, land and soil health, water resources and biodiversity and altering the nutrient cycles to the detriment of ecosystem wealth at the landscape level. Livestock farming poses significant environmental challenges, creating negative feedback loops with climate change that affect mitigation and adaptation efforts. Overgrazing damages the land, leading to poor soil quality and reduced productivity (Asner et al. 2004), while pasture expansion contributes to deforestation, destroying habitats and exacerbating climate change (Pendrill et al. 2019). Recent estimates suggest that livestock production accounts for approximately 11% of global greenhouse gas emissions, a reduction from previous estimates of 14.5% (Poore and Nemecek 2018). In 2015, livestock agri-food systems emitted around 6 billion tonnes of CO2 equivalent, with projections indicating that emissions could rise to nearly 9 billion tonnes by 2050 without significant interventions (FAO 2023). Agriculture contributes 40% of the global human-caused methane emissions, of which the largest part (32%) comes from manure and enteric fermentation from livestock (CCAC and UNEP 2021). Due to population and income growth, the demand for livestock is expected to increase by up to 70% by 2050 (Ranganathan 2018), which, unabated, will increase methane emissions proportionally. This environmental footprint creates negative feedback loops with climate change, affecting mitigation and adaptation efforts. Deteriorating environmental health increases the vulnerability of livestock production and societies to climate change, limiting adaptation options and reducing overall productivity, which further drives up greenhouse gas emission intensities. As global demand for animal products rises, the environmental footprint of livestock is expected to grow, worsening these challenges. Reducing the environmental footprint of livestock production is critical to achieving global climate goals and mitigating the severe impacts of climate change and for maintaining the livelihoods of 1.7 billion people and 60% of rural households in developing countries. To address these challenge